"Constructing the We": Relational Reflexivity of Couples with Children in Italy. A Mixed-Method Study. Issue 5 (4th July 2022) - Moscatelli, Matteo; Ferrari, Chiara; Parise, Miriam; Serrano, Cecilia; Carrà, Elisabetta
ABTSRACT: Relational reflexivity (RR) is an increasingly important aspect in order to understand the agency of individuals and the couple's life, particularly in postmodern society. This mixed-methods research aimed to observe different dimensions of RR in 32 couples (25–40 years), married or cohabiting with at least one child, during the process of building the "we." Quantitative instruments (Perspective Taking Scale, Couple Generativity Scale, Quality of Marriage Index) together with semi-structured interviews with the administration of projective instruments (the family line and IOS scale) were used to collect information about this process. With the first set of results, the couples were classified into 3 groups with different levels of relational reflexivity (high, medium, and low). Each group had specific dynamics and ways to deal with the challenges of life as a couple. The construction of the "we" was a common process for all of them influenced by structural elements (marriage, cohabitation number of children and relationship duration) but couples differed in their communication processes, social resources, intergenerational relationships and ways of managing stressors. This study provides an innovative assessment of couples, based on their reflexivity, and suggestions for the development of new kinds of intervention to foster couple reflexivity.